PENGENALAN MANAJEMEN BISNIS SYARIAH MELALUI PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH DI DESA CIMANGGGU I, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Muhamad Syamsul Ma’arif; Ujang Buchori Muslim; Hasbi Ash Shiddieqy (SAHID EMPOWERMENT JOURNAL, 2021)
Abstract Spinach is a highly nutritious vegetable ingredient and is loved by all levels of society. Cimanggu I Village is one of the villages in Cibungbulang District, where most of the residents' livelihoods are in the agricultural sub-sector. One of the home industries in the area is the PKK women's group. These groups are cadres who work in the village to improve the field of business in Cimanggu I Village. The community service method is providing training to farmer groups or PKK cadres in Cimanggu I Village is a participatory method, which involves as many partners as possible in participating in discussion and practice activities that produce products. After doing this community service in the form of training on making spinach chips by partners or the community in Cimanggu I Village, they can find out that spinach that is not selling well and is still good or excessive from the harvest can be processed into spinach chips. These spinach chips can be easily managed as complementary foods and snacks, which were recently held in Cimanggu I Village. Apart from being beneficial for health because of their high nutritional content, they can also be made as souvenirs that can increase farmers' daily income. And also with this training, it is able to help create business opportunities or be able to develop businesses for the people in Cimanggu I Village. Keywords: Spinach, Micro, Small and Medium Enterprises Development, Sharia Business Management.